Mengurai Keindahan Isti’arah: Analisis Struktur Retoris dan Fungsinya dalam Penafsiran Al-Qur’an - Megawati Megawati; Mohammad Harjum; Mardan Mardan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Studies of isti‘ārah in balāghah often limit themselves to formal definitions and classifications, so that its rhetorical function and role in interpreting the Qur’an have not been comprehensively explored. Previous studies generally treat isti‘ārah as a linguistic ornament, without linking it deeply to the formation of meaning and spiritual messages in verses. This weakness prompted this study to present an approach that emphasizes the integration between the structure of isti‘ārah and its rhetorical function in the interpretation of the Qur'an. The purpose of this study is to explain the concept, form, and function of isti‘ārah and its contribution in clarifying meaning, strengthening moral messages, and displaying the beauty of the language of the Qur'an. This study uses a qualitative-descriptive method through literature study and text analysis of Qur'anic verses. The results show that isti‘ārah plays an important role as a pedagogical, rhetorical, and aesthetic medium in the interpretation of the Qur'an. In conclusion, isti‘ārah is a primary instrument for meaning formation, not merely a figure of speech.